Mothers during the pandemic: the COVID-19 pandemic and online parenting group experiences of mothers - Erdivanlı, Zeynep Eda (İstanbul Bilgi Üniversitesi, 2021)
ABSTRACT: The parents’ experiences during the pandemic and the online parenting group experiences were explored in this study. Semi-structured interviews were separately conducted with nine mothers. In the narratives, the participants expressed the effects of the pandemic on their parenting, online parenting group experiences, and their suggestions for improving the online parenting group. Data analysis was carried out with the thematic analysis method, and four basic themes emerged as a result of the study. These were: Mothers’ perception of themselves and their spouses’ as a parent, Effects of the pandemic, Online Parenting Group (OPG) experience, and The OPG design. The study results showed that parents and their children were negatively affected by the pandemic, the workload of mothers increased during this process, the negative effect of gender-based disproportionate responsibility in parenting on mothers, and the importance of father involvement. In addition, the participants’ positive experiences regarding the online parenting group, such as sharing, feeling that they are not alone, and acquiring knowledge, showed the necessity of supportive parenting groups and the importance of the participation of both parents. The findings of this study provided valuable information for psychotherapists who work with children, adolescents, and families in online parenting. The limitations of this study were discussed and suggestions for future research were presented.

ÖZET: Bu çalışmada ebeveynlerin pandemi sürecindeki deneyimleri ve çevrimiçi ebeveynlik grubu deneyimleri incelenmiştir. Bu çalışmaya dokuz anne katılmıştır. Her bir katılımcı ile yarı yapılandırılmış görüşmeler yapılmıştır. Katılımcılar söylemlerinde pandeminin ebeveynliklerine olan etkilerini, çevrimiçi ebeveynlik grubu deneyimlerini ve çevrimiçi ebeveynlik grubunu geliştirmeye yönelik önerilerini ifade etmişlerdir. Veri analizi tematik analiz yöntemiyle gerçekleştirilmiş ve analiz sonucunda dört ana tema ortaya çıkmıştır: Bunlar: Annelerin kendilerine ve eşlerine yönelik ebeveynlik algısı, Pandeminin etkileri, Çevrimiçi ebeveynlik grubu deneyimleri ve Çevrimiçi ebeveynlik grubu tasarımı olarak isimlendirilmiştir. Çalışmanın sonuçları ebeveynlerin ve çocuklarının pandemiden olumsuz etkilendiğini, bu süreçte annelerin iş yükünün arttığını, ebeveynlikte cinsiyete dayalı orantısız sorumluluğun anneler üzerindeki olumsuz etkisini ve baba katılımının önemini göstermiştir. Ayrıca katılımcıların çevrimiçi ebeveynlik grubuna ilişkin paylaşım yapabilme, yalnız olmadıklarını hissetme ve bilgi edinme gibi olumlu deneyimleri destekleyici ebeveynlik gruplarının gerekliliğini ve bu gruplara her iki ebeveynin katılımının önemini ortaya koymuştur. Bu çalışmanın sonuçları, çocuk, ergen ve ailelerle çevrimiçi çalışan psikoterapistler için faydalı bilgiler sunmaktadır. Bu çalışmanın sınırlılıkları tartışılmış ve gelecek çalışmalar için öneriler sunulmuştur.
Pandemide anneler: COVİD-19 pandemisi ve annelerin çevrimiçi ebeveynlik grup deneyimleri
Keywords: Covid-19; pandemic and parenting; online parenting group; social support; father involvement; pandemi ve ebeveynlik; çevrimiçi ebeveynlik grubu; sosyal destek; baba katılımı